Comparison of the history obtained by patient-completed questionnaires with doctors' standard notes for patients with acute abdominal pain. Issue 1010 (14th January 2010) - Saravanan, B; Muhammad, R; Geach, R; Jenkinson, L R
Abstract : Background: Studies have shown that proformas improve the information recorded by junior doctors when they clerk patients with acute abdominal pain. This increases their diagnostic accuracy, but doctors are reluctant to use them. Patient-completed questionnaires are being used in elective surgery, but can they be used for patients with acute abdominal pain? Objective: To evaluate the history obtained by patient-completed questionnaires in patients with acute abdominal pain and compare this with the history recorded by the admitting junior doctors. Design: Prospective observational study. Subjects: 116 adult patients aged 17–90 admitted as an emergency to the Department of Surgery at Ysbyty Gwynedd in North Wales. Main outcome measures: Differences in the amount of information collected using patient-completed questionnaires and the history recorded by junior doctors. The questionnaires contained 17 points relating to general symptoms of the acute abdomen and five points related to gynaecological symptoms. Results: Of the 116 patients studied, 100 (86.2%) completed the questionnaires. There were 60 female and 40 male patients and the median age was 49 years (range 17–90). Doctors recorded fewer than 50% of the general symptoms for acute abdominal pain and patients recorded 90% or more (p<0.0001). Doctors' documentation of gynaecological symptoms was better, but still less detailed than patients' (52–76% vs 92–100%). Conclusion: Patient-completed questionnaires can be used to obtain a more accurate history than junior doctors for most patients admitted with acute abdominal pain.